Abraham's silence : the binding of Isaac, the suffering of Job, and how to talk back to God - Middleton, J. Richard., 1955- (Baker Academic; Grand Rapids, 2021)
"A widely respected scholar suggests we have misread and misapplied the story of the binding of Isaac and shows that God desires more than silent obedience in difficult times"--
Includes bibliographical references and index.
Keywords: Abraham -- (Biblical patriarch); Isaac -- (Biblical patriarch) -- Sacrifice; Job -- (Biblical figure); Bible. -- Criticism, interpretation, etc; Conversation -- Religious aspects -- Christianity; Prayer -- Biblical teaching